RehabilitacjaPatient with diabetes mellitus after coronary artery bypass surgery – challenge for cardiac rehabilitation - Karolewski, Marcin; Borowicz-Bieńkowska, Sławomira; Przywarska, Izabela; Dylewicz, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Patients with diabetes mellitus (DM) account for approximately 25-30% of the population of people undergoing coronary artery bypass graft surgery (CABG). Despite of undiscussed benefits received by diabetics after CABG, many science news indicates specific problems of that group of patients, includind increased rate of postoperative complications like: increased risk of wound infections, arrhytmias, neurological disorders, atelectasis, renal failure, optic neuropathy, what makes that group of patients constitute higher risk group for the cardiac rehabilitation. It doesn’t mean the group shouldn’t be qualified for intensive rehabilitation. In opposition, many indirect proves indicates good rehabilitation in that group of diabetics be especially efective. However, the rehabilitation in that group should be expanded and turned towards not only the physical exercises and modification of cardiovascular risk factors but the diagnosis and treatment suspected postoperative complications as well.